Altered carbon - Morgan, Richard K., 1965- (New York : Del Rey/Ballantine Books, 2003)
In the 25th century, humankind has spread throughout the galaxy, monitored by the watchful eye of the U.N. While divisions in race, religion, and class still exist, advances in technology have redefined life itself - a person's consciousness can be easily downloaded into a new body, making death nearly obsolete. Ex-U.N. envoy Takeshi Kovacs has been killed before, but his last death was particularly brutal. Resleeved into a new body in Bay City (formerly San Francisco), Kovacs is thrown into a shady, far-reaching conspiracy that is vicious even by the standards of a society that buys and sells human existence. As a warrior-for-hire, he is called to help a far-flung planet's government put down a bloody revolution. But when a rogue pilot and a sleazy corporate fat cat offer him a lucrative role in a treacherous treasure hunt, he's only too happy to go AWOL with a band of resurrected soldiers of fortune. All that stands between them and the ancient alien spacecraft they mean to salvage are a massacred city bathed in deadly radiation, unleashed nanotechnology with a million ways to kill, and whatever surprises the highly advanced Martian race may have in store.
Keywords: Private investigators -- Fiction; Soldiers of fortune -- Fiction; Rich people -- Fiction; Murder -- Investigation -- Fiction; Interstellar travel -- Fiction; Nanotechnology -- Fiction; Genetic engineering -- Fiction; Immortalism -- Fiction; San Francisco (Calif.) -- Fiction; Detective and mystery fiction; Science fiction